The Relationship Between Mothers' Knowledge Level about Exclusive Breastfeeding and Providing Exclusive Breastfeeding Behavior - Erfika Dyastuti Wanadi; Sri Wahyuningsih; Agustina Widayati; Sunanto (Health and Technology Journal (HTechJ), 2023)
Child health problems in Indonesia are affected by the high infant mortality rate (IMR). One of the reasons for the high infant mortality rate in Indonesia is the low level of breastfeeding immediately after birth (initiation of breastfeeding) and exclusive breastfeeding. This study aimed to determine the relationship between mothers' knowledge and exclusive breastfeeding in the working area of ​​the sub-district health center. This study used an analytic survey study using a cross-sectional method. Data was collected using a questionnaire with a sample of 81 mothers with children aged 0-6 months, taking samples with purposive sampling. Data were analyzed using the Chi-Square test. Characteristics of the last educational research respondents 30 (37%) had junior high school education. The employment status of housewives was 34 (42%), 21 (25.9%) private, and 15 (18.5%) farmers. The average maternal age at productive age was 20-35, namely 46 (56.8%) mothers. The level of knowledge of mothers about exclusive breastfeeding mostly has a sufficient level of understanding of as many as 39 (48.1%) mothers. Mother behavior of infants aged 0-6 months mostly gave exclusive breastfeeding to their babies, as many as 47 (58%) mothers. There is a significant relationship between mothers' knowledge level about exclusive breastfeeding and exclusive breastfeeding to infants aged 0-6 months in the working area of ​​the Krai health center with a p-value of 0.001. Mothers should actively ask midwives to explain the benefits of exclusive breastfeeding to motivate mothers to provide it to their babies.